Good intentions with adverse outcomes when conservation and pest management guidelines are ignored: A case study in rabbit biocontrol. Issue 4 (27th January 2022) - Taggart, Patrick L.; O'Connor, Tiffany W.; Cooke, Brian; Read, Andrew J.; Kirkland, Peter D.; Sawyers, Emma; West, Peter; Patel, Kandarp
Abstract: To mitigate the negative impacts of invasive rabbits in Australia, land managers are permitted to release the biocontrol virus, rabbit hemorrhagic disease virus (RHDV), to reduce rabbit numbers. However, it is strongly recommended that RHDV is not released when young rabbits are present in the population as infection in this cohort is sublethal and induces life‐long virus immunity. The recruitment of these rabbits into the breeding population may make the population harder to control in future, potentially leading to increasing rather than decreased population size. To investigate whether the recommended release guidelines are followed, we obtained data on the supply and release of RHDV by land managers. We then used generalized additive models to investigate Australia‐wide and state‐specific annual and long‐term temporal trends in the supply and release of RHDV. Half of all RHDV supply (47%) and three quarters of reported releases (74%) Australia‐wide occurred during the anticipated major rabbit breeding seasons and when the risk of immunizing young rabbits is greatest. We found evidence of both RHDV supply and release during the anticipated major rabbit breeding seasons in almost all states for which data existed. RHDV supply increased with below average annual rainfall. This may indicate a tendency for land managers to notice, and want to control, rabbits and their impacts more following drier years when both rabbits and their impacts are potentially more damaging. Our study raises concerns regarding the inappropriate release of RHDV by land managers and whether its supply should be restricted to ensure ongoing and effective management of invasive rabbits. More broadly, our study serves as a warning to other conservation and pest management activities reliant on land managers or citizens following implementation guidelines. In some cases, good intentions may have adverse outcomes. Abstract : Rabbit hemorrhagic disease virus release timing.